Χάνδακας Aller-retour (MCLab HMU, 2016)
: Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική Μουσική